From Fiction to History: The 1836 Execution of Indians (Quinto Sol, 2014)
In 1836 Governor Juan M. de Rosas is supposed to have ordered the execution of 110 pampa Indians in the main plaza of Buenos Aires city.This is what the anti-Rosista fiction argued: The “Tyrant” had executedindigenous peoples in order to cause terror on the Unitario opponents. Was this event a product of a political fiction? Or was it a true massacre of aboriginal peoples? The essay tries to respond to these questions, using both new archival sources, the testimonies provided at the trial of Rosas after his fall, and other secondary sources. At stake is the puzzling interaction or overlapping of historical and fictional narratives in the history of post-independent Argentina.
Keywords: violence; execution; natives; Juan Manuel de Rosas